Decoding terrorism: an interdisciplinary approach to a lone-actor case - Kupper, Julia (Cambridge elements Elements in forensic linguistics, 2024)
"This Element is an interdisciplinary analysis of the language evidence produced before, during and following a lone-actor terrorism attack in Halle, Germany, on October 9, 2019, resulting in two casualties. During his final preparations, the perpetrator, twenty-seven-year-old Stephan Balliet, announced his attack online and disseminated a targeted violence manifesto shortly before live-streaming his premeditated act. This post-hoc investigation introduces a multi-method approach that synchronizes well-established qualitative methodologies for forensic text analysis - genre, text linguistics, appraisal and uptake - to elucidate these data types. Furthermore, a retroactive threat assessment based on language data from the trial transcripts provides a holistic review of the assailant's background, red flags, triggering events and warning behaviors that could have signaled his movements along the pathway to violence. The results are considered in an organizational context to highlight current challenges faced by security agencies when mitigating the risk of lone-actors who radicalize in online environments"--